Biochemistry with exercises and tasks: учебник для использования в образовательных учреждениях, реализующих основные профессиональные образовательные программы высшего образования уровня специалитета по направлению подготовки 31.05.03 "Стоматология" - Глухов, А. И. Александр Иванович (Сеченовский университет, 2020)
The textbook written by the professors of the Biological Chemistry Department of the I.M. Sechenov First Moscow State Medical University (Sechenov University) approaches сomplicated modern scientific data about a molecular basis of the functioning of the organism in an intelligible form. This edition contains illustrative material, test tasks and situational problems in each of 14 sections. All the problems proposed for the individual solution have "guiding" questions that help students to solve them. Most of these tasks are based on the questions covered in the special course "Biochemistry of connective tissue. Biochemistry of mixed saliva". The textbook is intended for medical students who specialize in Dentistry, and can be also used for studying biochemistry by the students of other specialties.